Comprehensive and Measurable Environmental Monitoring: A Comparison of Indonesian and Danish Concepts - Annisa Fianni Sisma; Rahayu Subekti (Udayana Journal of Law and Culture, 2024)
Supervision is one of Indonesia's efforts to protect the environment, but its regulation still needs improvement. The reason is that the regulation does not cover broad authority for the Technical Authority, a comprehensive and measurable supervision scheme. Regulations regarding this matter significantly affect entrepreneurs' compliance levels to prevent or even increase environmental violations. Therefore, the regulation can be improved by studying it from Denmark. This study aims to provide an overview of environmental monitoring in Denmark to be used as a reference for regulatory changes in Indonesia. More comprehensive and participatory supervision regulations can significantly reduce environmental pollution and/or damage cases. This research is normative research with statutory and comparative approaches. The study suggests that several provisions in Denmark can be adopted, namely the extent of the authority of Danish Supervisory Officials starting from location, raw materials, and equipment used to product distribution and intervention against companies, stricter sanctions, and ensnare environmental violators, the authority to obtain personal information from other institutions, an excellent vertical integration system, and Supervisory Officials according to the number and background.